A comparison of electronic text readers utilizing metaphors in electronic text presentation - Palacios, Cheryl D. (2019)
The study aims to describe the various commercially and freely available electronic text readers which cover all or almost all of the dominant metaphors in electronic text presentation and gauge these readers against each other and against print. The data that has been gathered as a result of the study could be of significant use in the future development of electronic text readers and appliances, as well as in the improvement of existing metaphors and with which current electronic text readers and appliances currently operate.